State-of-the-art review of probabilistic seismic hazard analysis in Nepal: status, challenges, and recommendations - Kabin Lamichhane; Samana Bhattarai; K. C. Rajan; Keshab Sharma; Richa Pokhrel (Geoenvironmental Disasters)
Abstract Background This paper presents a state-of-the-art review of probabilistic seismic hazard analysis (PSHA) in Nepal. Over the years, numerous studies have estimated seismic hazards in terms of peak ground acceleration (PGA) and spectral acceleration (SA). However, the results often exhibit significant variation, contributing to uncertainty among engineers, designers, planners, and policy makers. This variation underscores the need for a critical evaluation of existing studies to identify the underlying factors driving these differences in hazard predictions and to provide informed guidance on the most appropriate estimates for practical application. Results This study systematically analyzes and compares multiple PSHA studies that have estimated seismic hazard either for the entire country or for specific urban regions within Nepal. The observed variation in hazard levels arises from several methodological differences. Key contributing factors include the selection of ground motion prediction equations (GMPEs), differences in seismic source characterization and zonation, assumptions regarding local soil conditions, the choice of computational tools and modeling approaches, methods of declustering earthquake catalogs, and the extent and quality of seismic data employed. More recent studies tend to incorporate updated earthquake catalogs, refined seismic source models, and improved regional data, thereby enhancing their relevance for the design of typical structures and for the preliminary assessment of large infrastructure projects. Notably, many of these newer studies report hazard levels that exceed those specified in the current Nepal National Building Code, suggesting that existing code provisions may underestimate the present-day seismic risk. Conclusion Improving the accuracy and reliability of future seismic hazard assessments in Nepal necessitates the development of region-specific GMPEs derived from locally recorded strong ground motion data. Incorporating comprehensive information on local geological conditions, active fault characteristics, and seismic source parameters, together with the application of advanced computational methods, can significantly enhance the precision of hazard estimates. Such improvements are critical for supporting safer structural design practices and for strengthening earthquake resilience across Nepal's seismically vulnerable regions.